The Influence Of GO SPIRIT Corporate Cultural Values On Customer Satisfaction Levels At Bank bjb Kcp Gedebage - Febri Adhaini; Adji, Widwi Handari (Yayasan Azka Hafidz Maulana, 2025)
This study analyzes the influence of GO SPIRIT's corporate culture on customer satisfaction at Bank bjb KCP Gedebage. Using a quantitative approach with a closed questionnaire on 60 respondents, data were analyzed through a statistical test using SPSS version 30. The results showed that the GO SPIRIT culture had a significant effect on customer satisfaction, with the values of f calculated (331,489) > f table (3,156) and t calculated (18,207) > t table (2,002). The determination coefficient of 92.3% indicates that customer satisfaction is influenced by company culture. Thus, the consistent implementation of the GO SPIRIT culture can increase customer satisfaction and loyalty.